An evaluation of a sheltered workshop program for workers with disabilities - Tempongko, Nilda Lucero- (College of Education, University of the Philippines Diliman, 2007)
The need for comprehensive information on current efforts and good practices related to the training and employment of persons with disabilities (PWD), is among the challenges faced by the PWD sector. This descriptive-evaluative study using W.K. Kellogg Foundation Project Level Evaluation Model investigated SIKAP to determine which factors of its program can contribute to the improvement of lives of workers with disabilities. The respondents were 15 workers, 4 managers and 2 trainers. It was revealed that positive effects of a sheltered workshop program in the lives of workers with disabilities are not limited to positive financial outcomes but include others as sense of independence, of self-worth and competence or productivity. There is a strong need for SIKAP therefore to continue their operation and seek for new approaches in order for its program to have real impact on the well-being of its workers with disabilities